RISING SUN: JAPAN’S FINANCIAL AND HUMANITARIAN AID TO UKRAINE AMIDST FULL-SCALE RUSSIAN AGGRESSION - Nazarko, Artem (Collection of scientific papers «ΛΌГOΣ», 2023)
This article examines Japan’s role in supporting Ukraine during the ongoing armed aggression. Drawing parallels between the historical experiences of both nations during World War II, the study delves into Japan’s transformation from aggressive militarism to a responsible global citizen. Through comprehensive analysis, the article explores the multifaceted aid provided by Japan to Ukraine, categorizing it into six domains: assistance to Ukraine, financial restrictive measures, trade restrictions, visa limitations, sanctions against Belarus, and measures related to the so-called Donetsk People’s Republic and Luhansk People’s Republic. The research details Japan’s efforts in providing various forms of assistance, including financial support, humanitarian aid, and trade limitations. It further highlights Japan’s commitment to supporting Ukraine’s rebuilding efforts, evident through substantial financial contributions. The study also delves into Japan’s diplomatic engagement and its call for unity in addressing Russia’s aggression against Ukraine. This article sheds light on Japan’s empathetic stance and its dedication to maintaining international law and human dignity, underscoring the significance of global solidarity in times of adversity.